An integrated high-throughput strategy enables the discovery of multifunctional ionic liquids for sustainable chemical processes. Issue 2 (14th December 2018) - Zhu, Anlian; Li, Lingjun; Zhang, Chi; Shen, Yutan; Tang, Mingjie; Bai, Lili; Du, Chunyan; Zhang, Suojiang; Wang, Jianji
Abstract : An integrated high-throughput strategy was developed to facilitate the fast identifications of multifunctional ionic liquids for sustainable chemical processes. Abstract : Development of new chemical processes with simplified reaction systems and work-up procedures is a challenging task. Although ionic liquids are a class of potential multifunctional compounds to simplify traditional chemical processes, their rational design is difficult due to complex interactions. In this work, a proof-of-concept strategy has been proposed to achieve an integration of high-throughput preparation of ionic liquids and in situ screening of their reaction-promoting performance in 96-well plates. The integrated approach then enables a facile identification of optimal ionic liquids from a 400-ionic liquid candidate pool to act as the solvent, the catalyst and the separating assistant, simultaneously, for carbonyl-azide cycloaddition reactions. Merits of the ionic liquids-based processes have been demonstrated not only in the convenient and efficient synthesis of 1, 2, 3-triazolyl compounds but also in the discovery of a new reaction for the chemical post-modification of free peptides.